English and Spanish from a distributional and quantitative perspective: Equivalences and contrasts - Santos, Pascual; Sánchez, Aquilino (Estudios Ingleses de la Universidad Complutense, 2011)
The similarities or differences people perceive while comparing two or more languages are always relative. However, the analysis of these linguistic contrasts can be formalized either from different angles and/or linguistic levels (phonetic/phonological, morphological, syntactic, semantic, pragmatic, diachronic, etc.), or from different research methodologies (inductive, deductive, descriptive, etc.). The purpose of this comparative study between Spanish and English is to offer, for the first time, objective and reliable quantitative data on the structure and structuring of the lexical inventory in both languages (lexical richness, lexical growth, types, frequency bands, lexical and functional types, most common types, type-length, etc.); and to approach the different underlying mathematical properties of Spanish and English. All the quantitative data were obtained from two equivalent linguistic corpora (in structure, composition and size: 20 million words): Cumbre (for Spanish) and Lacell (for English).